Geographic trends in team-based learning (TBL) research and implementation in medical schools - Hong, Jimmy Ming (2020)
Purpose: Team-based learning (TBL) is an active approach to learning that can be implemented in large enrolment classes. This study aims to document the extent of implementation of TBL in medical schools and characterize the geographic distribution in the trends of TBL research. Method: To examine the geographic distribution and curricula of medical schools from the published TBL literature, a systematic review of the Web of Science Core Collection was performed on articles published between 2000 and 2018. To fill in the gaps on implementation of TBL outside of the published literature, a questionnaire was developed and sent to a global network of TBL researchers and practitioners. The articles and questionnaire responses were assessed according to seven core design elements described in TBL implementation guidelines. Results: The systematic review yielded 69 journal articles, with 39 (56.52%) from schools that use TBL in their curriculum. Publications in earlier years were mainly from North America, although Asia is now a key driver in TBL research and implementation. The questionnaire which received 27 valid responses indicated that TBL in most schools (74.07%) feature all seven core elements. Both the systematic review and questionnaire revealed that TBL is used more in the pre-clinical curriculum, often as an adjunct to other teaching methods. Survey respondents cited reasons such as inertia and faculty preference for TBL's limited use. However, a few schools in the US and Singapore report using it extensively throughout the medical curriculum. Discussion: TBL is rapidly becoming established in Asia, hence more work needs to be done to uncover research and implementation in various non-English contexts. Factors that enable institutions to scale and sustain TBL as a main educational tool throughout the curriculum also merit further research.